Attentional capture and aging: implications for visual search performance and oculomotor control. - Kramer, Arthur F.; Hahan, Sowon; Irwin, David E. (Psychology & Aging, 1999)
Two studies examined potential age-related differences in attentional capture. Subjects were instructed to move their eyes as quickly as possible to a color singleton target and to identify a small letter located inside it. On half the trials, a new stimulus (i.e., a sudden onset) appeared simultaneously with the presentation of the color singleton target. The onset was always a task-irrelevant distractor. Response times were lengthened, for both young and old adults, whenever an onset distractor appeared, despite the fact that subjects reported being unaware of the appearance of the abrupt onset. Eye scan strategies were also disrupted by the appearance of the onset distractors. On about 40% of the trials on which an onset appeared, subjects made an eye movement to the task-irrelevant onset before moving their eyes to the target. Fixations close to the onset were brief, suggesting parallel programming of a reflexive eye movement to the onset and goal-directed eye movement to the target. Results are discussed in terms of age-related sparing of the attentional and oculomotor processes that underlie attentional capture. Reprinted by permission of the publisher.